An approximate arithmetic progression approach for image filtering technique / \c Bilal Charmouti - Charmouti, Bilal (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2018)
Based on the above problem statement, the objectives in this study are summarized as follows ; to develop the noise detection phase in the filtering process, which aims only to treats the corrupted pixels in the noisy image and keeps others uncorrupted pixels with same values ; to develop the noise suppression phase by changing the corrupted pixels by the most correct values. In order to reduce the difference between the restored image and the original image, visually and quantitatively ; to compare the performance of the proposed filtering technique with the performance of exciting techniques.